SOX4, an epithelial–mesenchymal transition inducer, transactivates ADAM28 gene expression and co‐localizes with ADAM28 at the invasive front of human breast and lung carcinomas. Issue 8 (7th June 2018) - Sasaki, Aya; Abe, Hitoshi; Mochizuki, Satsuki; Shimoda, Masayuki; Okada, Yasunori
Abstract : ADAM28 (a disintegrin and metalloproteinase 28) is abundantly expressed by carcinoma cells in the human breast and non‐small cell lung carcinomas, and plays a role in carcinoma cell growth and metastasis. Although Src is an inducer of ADAM28 gene expression through the PI3K/AKT/mTOR and MEK/ERK pathways, direct transcriptional regulators for ADAM28 gene expression remain unknown. In this study, we performed the luciferase reporter assay and found that SOX4 (SRY‐related HMG‐box 4), an inducer of epithelial–mesenchymal transition (EMT), is a transcriptional activator for the ADAM28 gene. This activation required the SOX4‐binding consensus sequence at the 5'‐untranslated region of the mouse and human ADAM28 genes. Forced expression of SOX4 promoted the ADAM28 gene expression and migration in human breast and lung carcinoma cell lines. In the human breast and lung carcinoma tissues, ADAM28 and SOX4 were co‐expressed at the invasive front of carcinoma cell nests. Our data demonstrate that SOX4 transactivates ADAM28 gene expression through direct binding to the ADAM28 promoter region and suggest the possibility that ADAM28 plays a role in invasion through SOX4‐mediated EMT in the human breast and lung carcinomas.